2010
DOI: 10.1097/tp.0b013e3181db09c4
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell and Islet Co-Transplantation Promotes Graft Revascularization and Function

Abstract: Our results demonstrate the improvement of islet graft morphology and function by co-transplantation with MSCs. This improvement is attributable, at least in part, to the promotion of graft revascularization mediated by MSCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
219
6
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 242 publications
(235 citation statements)
references
References 30 publications
8
219
6
2
Order By: Relevance
“…Compared with previous studies using immunodeficient animals [52,54], the duration of insulin independence in humanized mice was significantly reduced [79], suggesting the existence of immune rejection. However, the introduction of human immunity also led to GvHD, a fetal disease characterized by the attack to the recipient's major organs by the infused xenogeneic immunocytes.…”
Section: Introductioncontrasting
confidence: 73%
See 4 more Smart Citations
“…Compared with previous studies using immunodeficient animals [52,54], the duration of insulin independence in humanized mice was significantly reduced [79], suggesting the existence of immune rejection. However, the introduction of human immunity also led to GvHD, a fetal disease characterized by the attack to the recipient's major organs by the infused xenogeneic immunocytes.…”
Section: Introductioncontrasting
confidence: 73%
“…Other studies suggested that BMSCs may also differentiate into endothelial cells and directly assist the neo-vessel formation [53]. Silva et al reported the transdifferentiation of BMSCs into an endothelial phenotype in a canine ischemia model, which is supported by the report from Ito et al that BMSCs directly differentiate into a van-willebrand-factor-positive vascular endothelial cell type to improve the islet graft morphology and function [54]. However, these results should be explained cautiously because the new-formed vessels may arise from native BMSCs instead of infused BMSCs.…”
Section: Bmscs Support Islet Functionsupporting
confidence: 66%
See 3 more Smart Citations